EXPERIMENTAL PHYSICOCHEMICAL MODELING OF INTERACTIONS BETWEEN PHOTOTROPHIC MICROORGANISMS (ANOXIPHOTOBACTERIA AND CYANOBACTERIA) WITH TRACE ELEMENTS IN AQUEOUS SOLUTIONS - Pokrovsky O.S.; Kompantseva E.I. (My University, 2007)
One of the most challenging tasks of modern environmental geochemistry is the quantitative modeling of trace-element fluxes (including those of heavy and toxic metals) in the water shell of continents. The major physicochemical factor controlling the migration of trace elements in natural waters is the adsorption of these elements on the surface of solid phases, coprecipitation with newly formed mineral components, and the active or passive consumption by microorganisms. Modern experimental studies and physicochemical descriptions of the interactions of trace elements with inorganic components of natural waters are now at the level of theoretical modeling and have a high prediction potential. At the same time, quantitative physicochemical approaches to the modeling of the influence of a biota on the cycles of chemical elements are developed inadequately. The few past decades witnessed the mushrooming of publications (mostly in English) devoted to studying the reversible (equilibrium) interaction of ecologically significant metals (Cd, Zn, Pb, and U) with the surfaces of bacteria.